ANALYSIS STUDY OF CLOVE LEAF (SYZYGIUM AROMATICUM) EXTRACT ABSORBANCE USING UV-VIS SPECTROPHOTOMETER: STUDI ANALISIS ABSORBANSI EKSTRAK DAUN CENGKEH (SYZYGIUM AROMATICUM) MENGGUNAKAN UV-VIS SPECTROPHOTOMETER - Natasya Frysilia Wardanni; Iwan Sugihartono; Anggara Budi Susila; Rahmat Setiawan Mohar (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This study reports that clove (Syzygium aromaticum) leaf extract was used as a reducing agent and deionized water was used as a solvent. In the process of making the extract, as much as 20 grams of clove leaf powder was mixed with 100 mL of deionized water and boiled using a hotplate magnetic stirrer for 2 hours at a temperature of 70°C. Then, the extract solution was filtered using 11 cm diameter filter paper and centrifuged at 4000 rpm for 30 minutes to obtain clove leaf extract. The extract was characterized using UV-Vis Spectrophotometer to analyze the absorbance and energy band gap. Based on the absorbance test results, clove leaf extract showed maximum absorption at a concentration of 1000 ppm with a wavelength of 221 nm and at a concentration of 500 ppm with a wavelength of 225 nm. The energy band gap value at a concentration of 1000 ppm is 3.26 eV and at a concentration of 500 ppm 3.38 eV.